Beyond Service: How Altruism and Gratitude Fuel Volunteers' Flourishing? - Lailatul Badi'ah; Dearly; Agus Mulyana (Merpsy Journal, 2025)
Indonesia possesses the world’s largest volunteer population, yet the act of volunteering often requires significant sacrifices of personal resources that can impact individual well-being. This study investigates the influence of altruism and gratitude as predictors of flourishing among volunteers in the Special Capital Region of Jakarta. Using a quantitative approach and a predictive correlational design, data were gathered from 228 respondents through accidental sampling. Flourishing was measured using The Flourishing Scale, while altruism and gratitude were assessed using the Generative Altruism Scale and the Gratitude Questionnaire–6, respectively. Multiple linear regression analysis demonstrated that both altruism and gratitude significantly and positively influence flourishing. Individually, altruism accounts for 23.4% of the variance in flourishing, while gratitude explains a substantial 65.7%. When combined, these variables account for 66.6% of the total variance. These findings suggest that fostering altruism and gratitude is essential for sustaining the psychological thriving of individuals within the volunteer sector.